Indium-111-Labelled Human Platelets: A Method for Use in Severe Thrombocytopenia - Heyns, A du P; Badenhorst, P N; Wessels, P; Pieters, H; Kotzè, H F; Lötter, M G (Thrombosis and Haemostasis, 1984)
We describe and evaluate a simple method for labelling autologous human platelets with Indium-111-oxine in patients with severe thrombocytopenia. Twenty patients with immune thrombocytopenia and platelet counts ranging from 5 to 119 × 109/1 were investigated. Platelets were isolated from blood by differential centrifugation, residual platelets were repeatedly washed from the red cell layer and buffy coat and labelled with In 111 in saline. A mean of 55% ± 21 of platelets were harvesteo from the blood, labelled with 49% ± 24 efficiency and 15.8 × 108 labelled platelets reinjected to the patients. Contamination of the platelets with red cells and plasma was low. The labelled platelets were viable as assessed by in vitro aggregation, recovery in the circulation and mean survival time. This method permits quantitative platelet imaging with autologous labelled platelets in patients with severe thrombocytopenia.
Keywords: Indium-111-labelled platelets; Platelet labelling in thrombocytopenia; Platelet label method